PHYSICAL EXERCISE IN PATIENTS WITH DIABETIC PERIPHERAL NEUROPATHY: A CASE STUDY - Dwiastuti, Riani; Rahman, Farid (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Diabetic peripheral neuropathy (DPN) is a common complication of long-term diabetes mellitus (DM) and is a progressive and irreversible disease. DPN occurs in 40%-59% of the total DM population, in general the estimated prevalence of DPN is 15.3-72.3/100,000 person-years, and in developing countries the prevalence of DPN is around 25-50%. Symptoms of DPN include paresthesias, hyperesthesia, and dysesthesias, and some patients experience neuropathic symptoms (such as burning and tingling) while others may have no signs or symptoms. Many disorders of the lower extremities and feet such as deformity, decreased range of motion, impaired balance coordination, and muscle weakness can be caused by DM. Physical therapy can improve the overall quality of life of DPN patients, and can relieve symptoms of diabetic neuropathy. It can also improve muscle strength, joint mobility, balance, coordination and physical function, when done regularly can reduce neuropathic pain and can help control blood sugar levels. Case Presentation: A 60-year-old woman with Diabetes Mellitus (DM) since 6 years ago (2015). Having complaints of numbness in both legs, these complaints more or less appeared in the last one year. Complaints get worse, especially when used to sit for a long time and stand for a long time, and complaints decrease when resting and walking at home. Management and Outcome: The physiotherapy program provided is in the form of stretching exercises for the lower extremities, balance (One leg stance, Side Lunges), gait training (Walking Exercise) and strengthening (Ankle theraband). Evaluation was carried out by measuring the value of numbness using NRS, measuring muscle strength in the lower extremities with the Five Time Sit to Stand Test, measuring static balance with MCTSIB and dynamically using the Time Up and Go Test. Discussion: Skeletal muscle stretching can help a person to control or lower blood glucose, this movement effectively has the benefit of exercising without physical stress. Gait and balance exercises with function-oriented strengthening programs are directed to simultaneously improve balance and gait in diabetic patients, exercise can improve macro and microvascular factors in diabetes. Strengthening exercises are important to reduce lower extremity weakness, which is a risk factor for falls in patients with DPN. Conclusion: The physiotherapy program which was conducted three times with stretching, balance, gait training and strengthening exercises was able to reduce the value of numbness in both legs.